Carbon nanotubes and graphene radiant heater printed on a cementitious flooring substrate: a feasibility study - Patsavellas, John; Salonitis, Konstantinos; Koziol, Krzysztof K.; Zakrzewski, Lukasz; Blackwood, Ben (SSRN, 2020)
The human activity of heating homes contributes a significant amount of CO2 in the total of the UK Green House Gases and the process of retrofitting residential stock and equipping new dwellings with lower and carbon neutral technologies could be complex, costly and physically challenging. This paper investigates the feasibility of a composite mixture of carbon nanotubes (CNT) and graphene material applied as a printed layer to the underside of a cementitious flooring substrate, acting as a radiant underfloor heater. Screening sample tests confirm instant radiant heating at low DC voltages with remarkably low conduction heat losses through the substrate.
Keywords: flooring; sustainable heating; Nanotubes; Graphene